The Managerial Roles of Ward and Unit Leaders and Their Correlation with Employee Burnout at Depok City Hospital During the COVID-19 Pandemic - Dwi Ayu, Della; Sujendra, Jendrawan Pati (Symbiohealth, 2025)
The COVID-19 pandemic placed heavy psychological demands on healthcare workers, increasing their vulnerability to burnout, with managerial functions of ward and unit leaders playing a critical role in shaping staff well-being. This study aimed to examine the relationship between managerial functions and employee burnout at Depok City Hospital. A cross-sectional analytical design was conducted in March 2022 involving 252 respondents randomly selected from a population of 534 employees. Data were collected via an online questionnaire covering demographics, managerial functions (planning, organizing, staffing, directing, controlling), and burnout dimensions (physical exhaustion, depersonalization, reduced personal accomplishment) based on the Maslach Burnout Inventory. Logistic regression analysis revealed that burnout levels were balanced, with 50.4% of respondents experiencing low burnout and 49.6% high burnout. Managerial function scores ranged from 50% to 63%, with directing achieving the highest score (63.1%). Multivariate analysis identified directing as the most significant predictor of burnout (AOR 3.363; 95% CI 1.956–5.78). These findings indicate that the directing function is the dominant managerial factor influencing burnout, and strengthening direction through regular meetings, effective communication, and alignment of standard operating procedures with staff responsibilities may help reduce burnout risk and improve workforce resilience.